A tale of H syndrome with typical radiographic findings - Praneet Pradeep Awake; Lakshmi Chandravathi Penmetcha; Anil Fonseca; Prasad Prabhakar Jawalkar (Wolters Kluwer Medknow Publications, 2018)
H syndrome is a recently described autosomal recessive genodermatosis with cutaneous phenotypes of varying severity and multi-system involvement. Patients suffering from this disorder can be easily mistaken for sclerodermoid conditions. The radiological findings of H syndrome are typical but have been described only anecdotally. We present a case of a 29 year old male patient of H syndrome with typical radiological features.